Text as a Tool for Organizing Moving Image Collections - Turner, James M.; Hudon, Michèle; Devin, Yves (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
In the rapidly-growing networked environment, it is critical to develop common methods for shot-level and scene-level description of moving image documents, in order to foster discovery and retrieval of these resources worldwide. In this paper, we describe the methodology used and report preliminary results obtained in a project designed to study existing tools for indexing moving images at the shot level. A number of institutions holding moving image collections were recruited as partners, and visits to them were then made to complete a questionnaire and gather other information during a structured interview. Preliminary results show that a variety of tools are used for indexing moving images, and that those institutions which have been able to invest in building good indexing tools over the years have seen the quality of those tools suffer in the wake of cutbacks in resources needed to maintain them.